Business Strategy Analysis of Cocoa Agribusiness Commodity Export Company at Agro Tama - Marina Diah Hapsari; Musran Munizu; Abdul Razak Munir (International Journal of Social Service and Research, 2022)
Cocoa, which is known as one of the people's plantations, is one of the commodities that has a positive contribution during the Covid-19 pandemic. The positive results of macro data related to the contribution of agriculture, especially cocoa to Indonesia's income during the pandemic, in fact experienced problems in raw materials which experienced a gradual decline in productivity in recent years, and also affected the productivity of several domestic cocoa companies. The decline in raw materials and the COVID-19 pandemic that has occurred since the end of 2019 also added to other problems faced by agricultural commodity export companies, including Agro Tama. Agro Tama is a domestic export company located in Makassar City which has been established for more than 20 years and contributes to the Indonesian economy through the export of cocoa beans. This study aims to analyze the company's internal and external factors, namely Strength, Weakness, Opportunity and Threat to produce an alternative strategy that is right for the company's condition. The results of the SWOT analysis show that the company's condition is in quadrant III strategy, namely WO (Weakness Opportunity) and produces 4 alternative strategies which are then analyzed again using the Analytical Hierarchy Process model. The results of the AHP analysis resulted in a proposed priority strategy, namely optimizing the company's export commodity diversification, with the main objective of the analysis model being the company's business development during the pandemic with a weight of 0.303.